Enabling Collaboration in Learning Computer Programing Inclusive of Children with Vision Impairments - Thieme, Anja; Morrison, Cecily; Villar, Nicolas; Grayson, Martin; Lindley, Siân (DIS 2017, 2017)
We investigate how technology can support collaborative learning by children with mixed-visual abilities. Responding to a growing need for tools inclusive of children with vision impairments (VI) for the teaching of computer programing to novice learners, we explore Torino – a physical programing language for teaching programing constructs and computational thinking to children age 7-11. We draw insights from 12 learning sessions with Torino that involved five pairs of children with vision ranging from blindness to full-sight. Our findings show how sense-making of the technology, collaboration, and learning were enabled through an interplay of system design, programing tasks and social interactions, and how this differed between the pairs. The paper contributes insights on the role of touch, audio and visual representations in designs inclusive of people with VI, and discusses the importance and opportunities provided through the ‘social’ in negotiations of accessibility, for learning, and for self-perceptions of ability and self-esteem.
Best Paper